Korelasi nilai Homeostasis Model Assesment for Insulin Resistance (HOMA-IR) dan kadar vitamin D pada remaja dengan obesitas di Kota Denpasar, Bali, Indonesia - Luh Gede Yuliadewi NS; I Made Arimbawa; Ketut Suarta; I Gde Raka Widiana; Made Kardana; Ni Putu Veny Kartika Yantie; Komang Ayu Witarini (DiscoverSys Inc., 2021)
Background: Obesity during adolescence can developed into obesity in adulthood and will increase the risk of metabolic dissease sush as insulin resistance. Recent years the role of vitamin D begin to be connection with insulin resistance. Vitamin D plays a role in regulation of synthesis dan insulin secretions from pancreatic beta cells, increase peripheral and hepatic glucose uptake. In obesity there is decrease in vitamin D bioavailability that causes low levels of vitamin D. This study aimed to proves a correlation between insulin resistance and vitamin D levels in adolescents with obesity.Methods: A observational analytic research with crossestional design has been done in junior and senior high school in Denpasar. Adolescennts performed anthropometric screening covers weight, height, body mass index (BMI), obesity if BMI > 95th percentile of CDC 2000 curve. Examined vitamin D levels and insulin resistance through calculation of HOMA-IR levels. Sample size calculation with ? 0,05, correlation coefficient (r) set to 0,5 with minimum sampel size 50. Data were analyzed using SPSS versin 17 for Windows.Results: Anthropometric screening performed obtained 135 students (3,3%) with obesity. Mean of vitamin D levels was 18,9 ng/mL, 10 (20 %) classified as vitamin D insufficiency and 39 (78 %) vitamin D deficiencies. The average of HOMA-IR levels 3,84, 24 (48 %) with insulin resistance based on HOMA-IR levels. Correlation coefficient between HOMA-IR levels and vitamin D was obtained – 0,37 (p=0,007). There was significant difference of prevalence of insulin resistance between obese adolescent with vitamin D deficiency compared with insuficiency and suficiency group (OR=5.8; 95%CI=1.1-30.6; p=0.025).Conclusion: This study concluded that There is a moderate negative correlation between HOMA-IR levels and vitamin D in obese adolescents. Latar Belakang: Obesitas pada masa remaja berisiko menjadi obesitas pada masa dewasa dan meningkatkan risiko penyakit metabolik seperti resistensi insulin. Beberapa tahun terakhir peran vitamin D mulai dihubungkan dengan resistensi insulin. Vitamin D berperan dalam regulasi sintesis dan sekresi insulin oleh sel beta pankreas, meningkatkan uptake glukosa perifer dan hepatik. Pada obesitas terjadi penurunan bioavaibilitas vitamin D yang menyebabkan rendahnya kadar vitamin D. Penelitian ini bertujuan untuk membuktikan adanya korelasi antara kadar vitamin D dengan resistensi insulin pada remaja dengan obesitas.Metode: Penelitian ini merupakan penelitian observasional analitik dengan desain potong lintang pada remaja SMP dan SMA di kota Denpasar. Remaja dilakukan skrining antropometri meliputi berat badan, tinggi badan, Indeks Masa Tubuh (IMT). Diagnosis obesitas jika IMT > persentil 95 kurva CDC 2000. Dilakukan pemeriksaan kadar vitamin D darah dan resistensi insulin melalui perhitungan kadar HOMA-IR. Perhitungan besar sampel dengan ? 0,05 ( tingkat kemaknaan 0,95), koefesien korelasi (r) ditetapkan 0,5 dengan jumlah sampel minimal 50. Data dianalisis dengan SPSS versi 17 untuk Windows.Hasil: Skrining antropometri dilakukan pada 135 subyek (3,3%) dengan obesitas. Rerata kadar vitamin D 18,9 ng/mL, dimana 10 ( 20 %) tergolong insufiseiensi vitamin D dan 39 (79%) defisiensi vitamin D. Rerata kadar HOMA-IR 3,84, 24 (48 %) mengalami resistensi insulin berdasarkan kadar HOMA-IR. Besar koefesien korelasi antara kadar HOMA-IR dan kadar vitamin D didapatkan – 0,37 (nilai p 0,007). Terdapat perbedaan bermakna kejadian resistensi insulin antara kelompok remaja obesitas dengan status defisiensi vitamin D dan kelompok dengan status vitamin D pada kelompok sufisien dan insufisien (OR=5,8; 95%IK=1,1-30,6; p=0,025).Kesimpulan: Penelitian ini menyimpulkan terdapat korelasi negatif sedang antara kadar HOMA-IR dan kadar vitamin D pada remaja dengan obesitas.